2022
DOI: 10.1002/pat.5720
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of biodegradable hydrogels based on chitosan and poly(azomethine‐urethane) containing phenyl triazine for drug delivery

Abstract: A series of biodegradable hydrogels based on chitosan and polyurethanes was fabricated to be applied to the drug delivery application, and the fabricated hydrogels were characterized by using SEM, and FT‐IR techniques. Polyurethanes were also synthesized by using the different diisocyanates, and the diisocyanate's effect on the properties of the hydrogels was clarified. The mechanical and thermal properties, % swelling capacity, biodegradation, and hydrophilic or hydrophobic behaviors of the chitosan and polyu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…This may be because the electrostatic interaction formed between the amino group of chitosan in the hydrogel and the phospholipid component of the bacterial cell membrane causes damage to the bacterial cell membrane and inhibits the growth of the bacteria. [51] The antibacterial activity of the hydrogel has also been demonstrated in the inhibition circle test (Figure 10b). The growth of the bacteria on the agar plates indicated that the bacteria were in an active growth phase.…”
Section: Antibacterial Propertiesmentioning
confidence: 87%
“…This may be because the electrostatic interaction formed between the amino group of chitosan in the hydrogel and the phospholipid component of the bacterial cell membrane causes damage to the bacterial cell membrane and inhibits the growth of the bacteria. [51] The antibacterial activity of the hydrogel has also been demonstrated in the inhibition circle test (Figure 10b). The growth of the bacteria on the agar plates indicated that the bacteria were in an active growth phase.…”
Section: Antibacterial Propertiesmentioning
confidence: 87%